Response of methanogenic community and their activity to temperature rise in alpine swamp meadow at different water level of the permafrost wetland on Qinghai-Tibet Plateau - Cui, Hongpeng; Wang, Yanfa; Su, Xin; Wei, Shiping; Pang, Shouji; Zhu, Youhai; Zhang, Shuai; Ma, Chenjie; Hou, Weiguo; Jiang, Hongchen (Frontiers in Microbiology, 2023)
Wetlands are an important source of atmospheric methane (CH4) and are sensitive to global climate change. Alpine swamp meadows, accounting for ~50% of the natural wetlands on the Qinghai-Tibet Plateau, were considered one of the most important ecosystems. Methanogens are important functional microbes that perform the methane producing process. However, the response of methanogenic community and the main pathways of CH4 production to temperature rise remains unknown in alpine swamp meadow at different water level in permafrost wetlands. In this study, we investigated the response of soil CH4 production and the shift of methanogenic community to temperature rise in the alpine swamp meadow soil samples with different water levels collected from the Qinghai-Tibet Plateau through anaerobic incubation at 5°C, 15°C and 25°C. The results showed that the CH4 contents increased with increasing incubation temperature, and were 5-10 times higher at the high water level sites (GHM1 and GHM2) than that at the low water level site (GHM3). For the high water level sites (GHM1 and GHM2), the change of incubation temperatures had little effect on the methanogenic community structure. Methanotrichaceae (32.44-65.46%), Methanobacteriaceae (19.30-58.86%) and Methanosarcinaceae (3.22-21.24%) were the dominant methanogen groups, with the abundance of Methanotrichaceae and Methanosarcinaceae having a significant positive correlation with CH4 production (P < 0.01). For the low water level site (GHM3), the methanogenic community structure changed greatly at 25°C. The Methanobacteriaceae (59.65-77.33%) was the dominant methanogen group at 5°C and 15°C; In contrast, the Methanosarcinaceae (69.29%) dominated at 25°C, and its abundance showed a significant positive correlation with CH4 production (P < 0.05). Collectively, these findings enhance the understanding of methanogenic community structures and CH4 production in permafrost wetlands with different water levels during the warming process.